2005
DOI: 10.1158/0008-5472.can-04-3117
|View full text |Cite
|
Sign up to set email alerts
|

Hypersialylation of β1 Integrins, Observed in Colon Adenocarcinoma, May Contribute to Cancer Progression by Up-regulating Cell Motility

Abstract: Colon adenocarcinomas are known to express elevated levels of A2-6 sialylation and increased activity of ST6Gal-I, the Golgi glycosyltransferase that creates A2-6 linkages. Elevated ST6Gal-I positively correlates with metastasis and poor survival, and therefore ST6Gal-I-mediated hypersialylation likely plays a role in colorectal tumor invasion. Previously we found that oncogenic ras (present in roughly 50% of colon adenocarcinomas) up-regulates ST6Gal-I and, in turn, increases sialylation of B 1 integrin adhes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
262
3
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 298 publications
(278 citation statements)
references
References 46 publications
12
262
3
1
Order By: Relevance
“…Hypersialylation of β1 integrins can up-regulate cell motility in colon cancer. this increased negative charged properties of sialic acids was correlated with reduced adhesiveness of tumor cells and may be suitable for conformational change of integrin and enhances its function in cell-ecM interactions (33). similar studies have also indicated that increased sialylation could activate β1 integrin, mediate its adhesion to ecM proteins (34) and stimulating cell migration through host ecM (35).…”
Section: Discussionmentioning
confidence: 85%
“…Hypersialylation of β1 integrins can up-regulate cell motility in colon cancer. this increased negative charged properties of sialic acids was correlated with reduced adhesiveness of tumor cells and may be suitable for conformational change of integrin and enhances its function in cell-ecM interactions (33). similar studies have also indicated that increased sialylation could activate β1 integrin, mediate its adhesion to ecM proteins (34) and stimulating cell migration through host ecM (35).…”
Section: Discussionmentioning
confidence: 85%
“…For example, GnT-V, GnT-III, ST6GalNAc I, and ST6Gal-I directly modify carbohydrate structures on ␤ 1 integrin and affect integrin activity. [33][34][35][36] These changes in N-glycosylation 33,37 or O-glycosylation 36 of ␤ 1 integrin lead to altered cell morphologic features and behavior. B4GALNT3 modifies N-and O-glycans decorated with GlcNAc in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…In vulva squamous carcinomas, b1-integrin is overexpressed and required for the invasive pattern (Brockbank et al, 2005). Interestingly, post-transcriptional modification of b1-integrin contributes to colon cancer progression (Seales et al, 2005). Mechanisms underlying modified integrin expression are still unclear, and possibly involve some oncogenes (Schwartz, 1993).…”
Section: Discussionmentioning
confidence: 99%